Effects of essential mineral elements deficiency and supplementation on serum mineral elements concentration and biochemical parameters in grazing Mongolian sheep - Jin, Xiwei; Meng, Lingbo; Zhang, Rui; Tong, Mengjie; Qi, Zhi; Mi, Lan (Frontiers in Veterinary Science, 2023)
Traditional sheep grazing is the pillar industry and the main source of income for local herders in the Inner Mongolia Autonomous Region of China. However, grazing sheep often suffer from mineral deficiency. In the present study, the feeding experiment was performed on 84 grazing Wu Ranke sheep. After being divided into calcium (Ca), zinc (Zn), copper (Cu), cobalt (Co), manganese (Mn), and selenium (Se) treatment groups, they were fed with a mineral deficient diet for 60 days and then a mineral supplement diet for 41 days. Serum samples were collected three times, 10 concentrations of essential mineral elements and 15 concentrations/activity of biochemical parameters were measured to assess the effects of mineral deficiency and supplementation on the physical health of sheep. The results revealed that the sheep showed mineral Ca, Cu, Co, Mn, and Se deficiencies after feeding their respective mineral deficient diet. Deficiency in dietary Ca, Zn, Cu, Co, Mn, and Se may adversely affect the liver, myocardium and pancreas of sheep. The prompt supplementation of dietary Zn, Cu, Co, Mn, and Se may alleviate the damage caused to the liver, myocardium and pancreas, while that of dietary Ca improved energy generation. In conclusion, the adequate supplementation of dietary Ca, Zn, Cu, Co, Mn, and Se is essential for avoiding the impairment caused to the liver, myocardium and pancreas function of sheep by the deficiency in essential dietary minerals.